PREVALENSI DAN FAKTOR RISIKO STUNTING PADA BALITA 24-59 BULAN DI INDONESIA: ANALISIS DATA RISET KESEHATAN DASAR 2018 [PREVALENCE AND STUNTING RISK FACTORS IN CHILDREN 24-59 MONTHS IN INDONESIA: ANALYSIS OF BASIC HEALTH RESEARCH DATA 2018] - Aditianti Aditianti; Irlina Raswanti; Sudikno Sudikno; Doddy Izwardy; Sugeng Eko Irianto (Persagi, 2020)
ABSTRACT Stunting in children under five years old is still a health problem, mainly in developing countries. The objective of this study was to determine the risk factors associated with the nutritional status of children aged 24 - 59 months in Indonesia. This study used nationwide basic health research (Riskesdas) 2018 data. The study design was cross-sectional. Samples were children between the ages 24-59 months in Indonesia. The number of samples that have been analyzed was 10,128. The result of this study showed that the prevalence of stunting in children between the ages 24-59 months was 29.1 percent. Logistic regression analysis showed that the risk factors associated with stunting in children between the ages 24-59 months were the father's education (AOR 1,56; 95%CI 1,22-1,99), mother's education (AOR 1,44; 95%CI 0,89-1,23), mother’s body height (AOR 2,32; 95%CI 1,94-2,77), father's BMI (body mass index (AOR 1,15; 95%CI 0,98-1,36)), and location of birthplace(AOR 1,63; 95%CI 1,35-1,96). Need a promotion at posyandu and health facilities or through other social media about to prevent stunting. In addition, counseling on health and nutrition for prospective brides (CATIN) is also needed to be encouraged together with related agencies. ABSTRAK Masalah stunting pada anak balita masih menjadi masalah kesehatan terutama di negara berkembang. Penelitian ini bertujuan untuk mengetahui faktor risiko yang berhubungan dengan status gizi anak usia 24–59 bulan di Indonesia. Penelitian ini menggunakan data Riskesdas 2018. Desain penelitian adalah Cross-sectional. Sampel penelitian adalah anak berusia 24-59 bulan di Indonesia. Jumlah sampel yang dianalisis 10.128 balita. Hasil analisis menunjukkan prevalensi stunting pada anak usia 24-59 bulan adalah 29,1 persen. Hasil analisis regresi logistik menunjukkan bahwa faktor risiko yang berhubungan dengan stunting pada balita 24-59 bulan di Indonesia adalah pendidikan ayah (AOR 1,56; 95%CI 1,22-1,99), pendidikan ibu (AOR 1,44; 95%CI 0,89-1,23) tinggi badan ibu (AOR 2,32; 95%CI 1,94-2,77);, IMT ayah (AOR 1,15; 95%CI 0,98-1,36), dan tempat persalinan (AOR 1,63; 95%CI 1,35-1,96). Perlu adanya promosi di posyandu dan fasilitas kesehatan atau melalui media social lainnya tentang perlunya pencegahan stunting. Selain itu, diperlukan juga penyuluhan tentang kesehatan dan gizi bagi calon pengantin (CATIN) perlu digalakkan bersama dengan dinas terkait.